Method for homogenously growing tantalum-based compound thin films with high-quality interfaces on tantalum substrates or coatings

By using hydrothermal treatment methods to grow tantalum oxygen fluorine or other tantalum-based compound films at high-quality interfaces on tantalum substrates, the problem of defects in the interface between the tantalum-based compound films and substrates is solved, and rapid charge transfer and photo/electrochemical performance improvement are achieved.

CN115874168BActive Publication Date: 2025-03-21INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211551721.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-03-21
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

When growing tantalum-based compound films on tantalum substrates, due to different crystal structures and different thermal expansion coefficients, there are a large number of gaps and defects in the interface between the film and the substrate, hindering charge transfer and affecting photo/electrochemical properties.

Method used

A homologous metal compound film is precipitated in situ in the fluorine-containing precursor solution by hydrothermal treatment, and a tantalum oxygen fluorine or other tantalum-based compound film with (semi) co-uniform or high-quality interface with the tantalum matrix or coating is formed.

Benefits of technology

The construction of a high-quality interface between the tantalum matrix and the tantalum-based compound film is achieved, which promotes the rapid transfer of charge, improves the photo/electrochemical properties of the film, and simplifies the preparation process, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003981437620000011
    Figure HDA0003981437620000011
  • Figure HDA0003981437620000012
    Figure HDA0003981437620000012
  • Figure HDA0003981437620000021
    Figure HDA0003981437620000021
Patent Text Reader

Abstract

The present invention relates to the fields of photoelectrocatalysis, electrocatalysis, microelectronic devices and sensors, and specifically to a method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating. A metal tantalum substrate or coating is used as a precursor, and a homologous metal compound film with a high-quality interface with the tantalum substrate is in situ precipitated on its surface by hydrothermal treatment in a fluorine-containing precursor solution environment. A tantalum oxyfluoride film with a (semi) coherent interface with the tantalum substrate is obtained by heat treatment under a suitable atmosphere, and then a secondary heat treatment is performed under different atmospheres to obtain other tantalum compound films with a high-quality interface with the tantalum substrate. The present invention can effectively improve the interface between the tantalum-based compound film and the substrate, promote the efficient transfer of charge, and provide a new preparation method for high-performance materials in the fields of photoelectrocatalysis, electrocatalysis, microelectronic devices and sensors based on the development of tantalum-based functional films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of photoelectrocatalysis, electrocatalysis, microelectronic devices and sensors, and in particular to a method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating. Background Art

[0002] The construction of high-quality interfaces between functional films and substrates and between different functional films is of great significance in the fields of solar cells, photoelectrocatalysis and devices. High-quality interfaces effectively inhibit the formation of interface defects, reduce the recombination of charges and energy loss at the interface, and thus improve the efficiency of the device. Taking perovskite solar cells as an example, the hole extraction layer and the electron extraction layer form a high-quality interface with the light absorption layer, which can greatly improve the efficiency of solar cells. At present, through epitaxial growth, functional films with similar crystal structures can be grown on films or substrates to form high-quality two-phase interfaces. For example, a rutile phase TiO2 nanorod film array with the same tetragonal phase is epitaxially grown on a fluorine-doped SnO2 (FTO) substrate. This high-quality two-phase interface greatly improves the performance of the photoelectrochemical water splitting of the TiO2-based photoelectrode. For thin film materials with significant differences in crystal structure from the substrate, it is often necessary to introduce one or more substances with smaller crystal structure differences as an intermediate transition layer to construct a high-quality two-phase interface.

[0003] However, for tantalum-based compound films grown on tantalum (cubic structure) substrates, especially tantalum-based nitride (orthorhombic) films. Due to the significant difference in crystal structure and thermal expansion coefficients between the two, a large number of gaps and defects will exist at the interface between the obtained tantalum-based compound film and the tantalum substrate during the heat treatment process, which seriously hinders the rapid transfer of charges across the interface and restricts the photo / electrochemical properties of the obtained film. Therefore, the above-mentioned interface problem has always been an urgent problem to be solved for the commercial application of tantalum-based functional thin film materials. Summary of the invention

[0004] The purpose of the present invention is to provide a method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, thereby achieving the formation of a high-quality two-phase interface between the metallic tantalum substrate and the tantalum-based compound functional film, and providing a new preparation method for high-performance materials in the fields of photoelectrocatalysis, electrocatalysis, microelectronic devices and sensors developed based on tantalum-based functional films.

[0005] The technical solution of the present invention is:

[0006] A method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, wherein a metal tantalum substrate or coating is used as a precursor, and a homologous metal compound film with a high-quality interface with the tantalum substrate or coating is in situ precipitated on its surface by hydrothermal treatment in a fluorine-containing precursor solution environment; a tantalum oxyfluoride film with a coherent or semi-coherent interface with the tantalum substrate or coating is obtained by a primary heat treatment under different atmospheres; and other tantalum-based compound films with a high-quality interface with the tantalum substrate or coating are obtained by a secondary heat treatment under different atmospheres.

[0007] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating is that the tantalum substrate or coating is made of pure metal tantalum or tantalum-based alloy.

[0008] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, wherein the homologous metal compound is ammonia tantalum oxide fluoride [(NH4)2Ta2O3F6, (NH4)3TaOF6].

[0009] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating comprises a fluorine-containing precursor solution, wherein the solute is one of HF, NH4F, NH4HF2 or a mixture of two or more thereof, and the solvent is one of water, ethanol, ethylene glycol or a mixture of two or more thereof.

[0010] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating comprises a hydrothermal treatment process including a gas phase hydrothermal treatment and a conventional hydrothermal treatment, the hydrothermal treatment temperature is 80 to 250° C., and the holding time is 0.5 to 48 hours.

[0011] The method for homogenously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating is that the precursor substrate or coating treated with gas phase hydrothermal treatment is suspended above the solution, and the precursor substrate or coating treated with conventional hydrothermal treatment is immersed in the solution.

[0012] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, wherein the atmosphere for obtaining tantalum oxyfluoride by a single heat treatment includes one or a mixture of two or more gases of air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, and sulfur dioxide, the heat treatment temperature is between 100 and 800°C, the heat treatment time is between 5 minutes and 10 hours, and the heating rate is between 1 and 30°C / min.

[0013] The method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating comprises performing a secondary heat treatment on a tantalum oxyfluoride film having a coherent or semi-coherent interface with the tantalum substrate or coating under different atmospheres, wherein the treatment atmosphere comprises one or a mixture of two or more of air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, and sulfur dioxide, the treatment temperature is between 150 and 1200°C, the treatment time is between 15 min and 48 h, and the heating rate is between 1 and 20°C / min.

[0014] The design ideas of the present invention are as follows:

[0015] Both metal tantalum (Ta) and tantalum oxyfluoride (TaO2F) have cubic crystal structures and similar unit cell parameters. Theoretically, a (semi) coherent interface can be formed between the two. Studies have found that ammonia tantalum oxyfluoride is composed of tantalum oxyfluoride octahedrons and intercalated ammonium ions, while the basic unit of tantalum oxyfluoride is tantalum oxyfluoride octahedrons. Tantalum oxyfluoride can also be prepared by removing the ammonium ions in ammonia tantalum oxyfluoride through heat treatment. Therefore, the tantalum substrate is etched in a fluorine-containing solution environment to form tantalum-based oxyfluoride. The construction of a (semi) coherent interface at the interface between the tantalum substrate and the tantalum oxyfluoride film can accelerate the transfer of charges. At the same time, the formation of a (semi) coherent interface can inhibit the formation of a large number of gaps at the interface between the tantalum substrate and the tantalum-based compound film in the subsequent heat treatment. Therefore, in the subsequent heat treatment, a tantalum-based compound film with a high-quality interface is obtained on the tantalum substrate.

[0016] The advantages and beneficial effects of the present invention are:

[0017] 1. The present invention synthesizes fluorine-containing tantalum-based compound precursors through hydrothermal and other wet chemical methods, and after simple heat treatment, forms a tantalum oxyfluoride film that is (semi) coherent with the tantalum substrate, thereby solving the problem of low-quality interface between the tantalum substrate and the tantalum-based compound film, and promoting the development of high-efficiency tantalum-based functional thin film electrodes for photoelectric catalysis and devices.

[0018] 2. The synthesis method adopted by the present invention is environmentally friendly, has simple steps, and is conducive to large-scale production.

[0019] 3. The tantalum oxyfluoride film with a (semi-) coherent interface obtained by the present invention solves the problem of interface gaps existing in tantalum nitride electrodes supported by a tantalum substrate.

[0020] 4. The tantalum oxyfluoride film with a (semi) coherent interface obtained by the present invention can be effectively treated with functionalization to reduce energy consumption and improve charge transport capacity in the fields of electrocatalysis, electrocatalysis, and microelectronics.

[0021] 5. The tantalum oxyfluoride film with a (semi) coherent interface obtained by the present invention is expected to improve its sensitivity as a photodetector and a gas sensor due to the rapid transfer of interface charges. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 .XRD spectrum of the obtained micron-conical ammonia tantalum oxyfluoride [(NH4)2Ta2O3F6] thin film supported by the metal tantalum substrate, with the abscissa being the diffraction angle 2θ (degree) and the ordinate being the diffraction peak intensity (au).

[0023] Figure 2 .XRD spectrum of the obtained micron-cone tantalum oxyfluoride (TaO2F) film supported by the metal tantalum substrate, the abscissa is the diffraction angle 2θ (degree), and the ordinate is the diffraction peak intensity (au).

[0024] Figure 3 .Scanning electron microscope (SEM) photograph of the cross section of the obtained micron-conical ammonia tantalum oxyfluoride [(NH4)2Ta2O3F6] thin film supported by the metal tantalum substrate.

[0025] Figure 4 .Scanning electron microscope (SEM) image of the cross section of the obtained micro-cone tantalum oxyfluoride (TaO2F) film supported by the metal tantalum substrate.

[0026] Figure 5 .The UV-visible absorption spectrum of the obtained micron-cone tantalum oxyfluoride [(NH4)2Ta2O3F6] film supported by the metal tantalum substrate, the horizontal axis represents the wavelength (nm) and the vertical axis represents the absorbance (au).

[0027] Figure 6 . Transmission electron microscope (TEM) image of the interface between the obtained metallic tantalum and micro-cone tantalum oxyfluoride (TaO2F) film.

[0028] Figure 7 .Scanning electron microscope (SEM) photograph of the top view of the obtained micro-cone tantalum oxyfluoride [(NH4)2Ta2O3F6] film supported by the metal tantalum substrate.

[0029] Figure 8 .Scanning electron microscope (SEM) photo of the top view of the obtained micron-cone tantalum nitride (Ta3N5) film supported by the metal tantalum substrate.

[0030] Fig. 9 .Cross-sectional scanning electron microscope (SEM) image of the obtained micron-cone tantalum nitride (Ta3N5) film supported by the metal tantalum substrate.

[0031] Fig.10 .XRD spectrum of the obtained micron-cone tantalum nitride (Ta3N5) film supported by the metal tantalum substrate, with the abscissa being the diffraction angle 2θ (degree) and the ordinate being the diffraction peak intensity (au).

[0032] Fig.11.The obtained ultraviolet-visible absorption spectrum of the micron-conical tantalum nitride (Ta3N5) film supported by the metal tantalum substrate, the horizontal axis represents the wavelength (nm) and the vertical axis represents the absorbance (au).

[0033] Fig.12 The original performance of the obtained micro-cone tantalum nitride (Ta3N5) film supported by the metal tantalum substrate and the photocurrent polarization curve under the sacrificial agent, the horizontal axis represents the reversible hydrogen potential (V), and the vertical axis represents the photocurrent density (mA / cm 2 ).

[0034] Fig.13 .Scanning electron microscope (SEM) photo of the top view of the obtained nanocone tantalum-ammonia-tantalum-oxyfluoride [(NH4)2Ta2O3F6] film supported by the metal tantalum substrate.

[0035] Fig.14 .Scanning electron microscope (SEM) image of the top view of the obtained nanocone tantalum oxyfluoride (TaO2F) film supported by the metal tantalum substrate.

[0036] Fig.15 .Scanning electron microscope (SEM) photo of the top view of the nanocone tantalum nitride (Ta3N5) supported by the obtained metal tantalum substrate. DETAILED DESCRIPTION

[0037] In the specific implementation process, the present invention provides a method for homologously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, using a metal tantalum substrate or coating as a precursor, and in a fluorine-containing precursor solution environment, hydrothermal treatment is used to in-situ precipitate a homologous metal compound (such as ammonia tantalum oxyfluoride / (NH4)2Ta2O3F6) film with a high-quality interface with the tantalum substrate or coating on its surface, and the thickness thereof is 0.5 to 10 microns. A tantalum oxyfluoride (TaO2F) film with a (semi-) coherent interface with the tantalum substrate or coating is obtained by a primary heat treatment under an appropriate atmosphere, and the thickness thereof is 0.5 to 10 microns; and then a secondary heat treatment is performed under a different atmosphere (such as ammonia) to obtain other tantalum-based compound films with a high-quality interface with the tantalum substrate or coating, and the thickness thereof is 0.5 to 10 microns. Among them, the specific features are:

[0038] 1. The tantalum substrate or coating is pure metal tantalum or tantalum-based alloy;

[0039] 2. The fluorine-containing precursor solution includes various fluorine-containing precursor solutions, the solute is one or a mixture of two or more of HF, NH4F, NH4HF2, etc., and the solvent is one or a mixed solvent of two or more of water, ethanol, ethylene glycol, etc.;

[0040] 3. The hydrothermal treatment process includes gas phase hydrothermal treatment (precursor substrate or coating is suspended above the solution) and traditional hydrothermal treatment (precursor substrate or coating is immersed in the solution), the hydrothermal treatment temperature is 80-250°C, and the holding time is 0.5-48h;

[0041] 4. The atmosphere for obtaining tantalum oxyfluoride (TaO2F) by the primary heat treatment includes one or a mixture of two or more gases such as air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, sulfur dioxide, etc., the heat treatment temperature is between 100 and 800°C (preferably between 300 and 500°C), the heat treatment time is between 5min and 10h (preferably between 0.5h and 3h), and the heating rate is between 1 and 30°C / min (preferably between 2 and 10°C / min);

[0042] 5. The tantalum oxyfluoride (TaO2F) film having a (semi) coherent interface with the tantalum substrate or coating is subjected to secondary heat treatment under different atmospheres, wherein the treatment atmosphere includes one or a mixture of two or more gases such as air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, sulfur dioxide, etc., the treatment temperature is between 150 and 1200°C (preferably 600 to 1000°C), the treatment time is between 15min and 48h (preferably between 0.5h and 8h), and the heating rate is between 1 and 20°C / min (preferably between 2 and 10°C / min).

[0043] The present invention is further described in detail below through examples and drawings. Example 1

[0044] Using a commercial tantalum substrate, first measure 10 mL of ethylene glycol and 1 mL of water, then weigh 50 mg of ammonium hydrogen fluoride (chemical formula NH4HF2), stir for a while, transfer the solution to an 80 mL stainless steel reactor lined with polytetrafluoroethylene, put in a sample holder, and then place the tantalum substrate on the sample holder. After the reactor is sealed, put it in an oven and heat it at 140°C for 7 h. Take out the reaction sample, wash it with ethanol and deionized water in turn, and blow it dry with nitrogen to obtain a micron-conical ammonia tantalum oxyfluoride film (chemical formula (NH4)2Ta2O3F6) supported by a tantalum substrate with a thickness of 5 microns. After being treated in an air atmosphere at 400°C for 2 h with a heating rate of 2°C / min, a tantalum oxyfluoride (chemical formula TaO2F) film supported by a tantalum substrate was obtained with a thickness of 5 microns, and a semi-coherent interface was formed between the tantalum substrate and the tantalum oxyfluoride film.

[0045] like Figure 1As shown, the XRD spectrum of the micron-conical ammonia tantalum oxyfluoride film supported by the obtained metal tantalum substrate shows that the metal tantalum substrate is a cubic structure, and a pure phase orthorhombic structure ammonia tantalum oxyfluoride film is obtained.

[0046] like Figure 2 As shown, the XRD spectrum of the micron-cone tantalum oxyfluoride film supported by the obtained metal tantalum substrate shows that the metal tantalum substrate is a cubic structure, and a tantalum oxyfluoride film with a pure phase cubic structure is obtained.

[0047] like Figure 3 As shown, the SEM photograph of the thin cross-section of the micron-conical ammonia tantalum oxyfluoride film supported by the obtained metal tantalum substrate shows that the obtained metal tantalum substrate and the ammonia tantalum oxyfluoride film form a close contact interface.

[0048] like Figure 4 As shown, the SEM photograph of the thin cross-section of the micron-cone tantalum oxyfluoride film supported by the obtained metal tantalum substrate shows that the obtained metal tantalum substrate and the ammonia tantalum oxyfluoride film form a close contact interface.

[0049] like Figure 5 As shown, the UV-visible absorption spectrum of the micron-cone tantalum oxyfluoride film supported by the obtained metal tantalum substrate shows that the obtained tantalum oxyfluoride film has an obvious absorption edge, and the absorption edge is located at 320nm.

[0050] like Figure 6 As shown, from the transmission electron microscope photograph of the interface between the obtained metal tantalum and the micron-cone tantalum oxyfluoride film, it can be seen that the obtained metal tantalum substrate and the ammonia tantalum oxyfluoride film form a (semi) coherent interface. Example 2

[0051] The micron cone-shaped ammonia tantalum oxyfluoride film (chemical formula: (NH4)2Ta2O3F6) supported by the metal tantalum substrate has a thickness of 5 microns. After a heat treatment, i.e., 450 ℃ air atmosphere treatment for 2 h, heating rate of 5 ℃ / min, a tantalum oxyfluoride (chemical formula: TaO2F) film supported by the tantalum substrate with a thickness of 5 microns was obtained; then the obtained tantalum oxyfluoride film supported by the tantalum substrate was subjected to a secondary heat treatment, i.e., treatment under ammonia gas at 1000 ℃ for 6 h, ammonia gas flow rate of 50 sccm, heating rate of 10 ℃ / min, to obtain a tantalum nitride (Ta3N5) film with a high-quality two-phase interface with the tantalum substrate, with a thickness of 5 microns.

[0052] like Figure 7 As shown, from the top-down scanning electron microscope photograph of the micron-cone tantalum oxyfluoride film supported by the obtained metal tantalum substrate, it can be seen that the obtained tantalum oxyfluoride micron-cone film has uniform size, a length of 5 microns, and a maximum width of the cone of 1.5 microns.

[0053] like Figure 8As shown in the top view scanning electron microscope photo of the micron cone tantalum nitride film supported by the obtained metal tantalum substrate, it can be seen that the morphology of the obtained tantalum nitride is similar to Figure 7 The tantalum oxyfluoride microcone films obtained are basically consistent.

[0054] like Fig. 9 As shown, from the SEM photograph of the cross section of the obtained metal tantalum substrate supporting the micro-cone tantalum nitride film, it can be seen that the obtained metal tantalum substrate and the tantalum nitride film form a two-phase interface with high-quality contact.

[0055] like Fig.10 As shown, from the XRD spectrum of the obtained metal tantalum substrate supporting the micron-cone tantalum nitride film, it can be seen that compared with the direct preparation of tantalum nitride film by one heat treatment of ammonia tantalum oxyfluoride, the tantalum oxyfluoride film is first heat-treated to obtain the tantalum oxyfluoride film, and then the tantalum oxyfluoride film is heat-treated to prepare tantalum nitride. The tantalum dinitrogen content at the interface of the obtained film is significantly increased, indicating the formation of a high-quality two-phase interface between the metal tantalum substrate and the tantalum nitride film.

[0056] like Fig.11 As shown, the UV-visible absorption spectrum of the micro-cone tantalum nitride film supported by the obtained metal tantalum substrate shows that the obtained tantalum oxyfluoride film has an obvious absorption edge, and the absorption edge is located at 600 nm.

[0057] like Fig.12 As shown, the original performance of the micron-cone tantalum nitride (Ta3N5) film supported by the obtained metal tantalum substrate and the photocurrent polarization curve under the sacrificial agent show that the original tantalum nitride performance is as high as 2.2 milliamperes per square centimeter, which is the highest value reported so far. At the same time, the current density under the sacrificial agent can reach 90% of the theoretical value. Example 3

[0058] Using a commercial tantalum metal substrate, first measure 10 mL of ethylene glycol and 1 mL of water, then weigh 20 mg of ammonium hydrogen fluoride (chemical formula NH4HF2), stir for a while, transfer the solution to an 80 mL stainless steel reactor lined with polytetrafluoroethylene, put in a sample holder, and then place the tantalum metal substrate on the sample holder. After the reactor is sealed, it is placed in an oven and heated at 160°C for 6 h. The reaction sample is taken out, washed with ethanol and deionized water in turn, and dried with nitrogen to obtain a nano-conical ammonium tantalum oxide fluoride film (chemical formula (NH4)2Ta2O3F6) supported by a tantalum metal substrate with a thickness of 2 microns. After a primary heat treatment, i.e., treatment at 450°C in air atmosphere for 1h with a heating rate of 2°C / min, a tantalum oxyfluoride (chemical formula: TaO2F) film supported by a tantalum substrate was obtained with a thickness of 2 microns; the obtained tantalum oxyfluoride film supported by a tantalum substrate was then subjected to a secondary heat treatment, i.e., treatment at 1000°C in ammonia for 1h with an ammonia flow rate of 50 sccm and a heating rate of 10°C / min, to obtain a tantalum nitride (Ta3N5) film with a high-quality two-phase interface with the tantalum substrate with a thickness of 2 microns.

[0059] like Fig.13 As shown, the top view scanning electron microscope (SEM) photograph of the nanocone tantalum ammonia tantalum oxygen fluoride film supported by the obtained metal tantalum substrate shows that the obtained ammonia tantalum oxygen fluoride nanocone film has uniform size, a length of less than 1000 nanometers, and a maximum width of the cone of less than 500 nanometers.

[0060] like Fig.14 As shown in the top view scanning electron microscope (SEM) photograph of the nanocone tantalum oxyfluoride (TaO2F) film supported by the obtained metal tantalum substrate, it can be seen that the morphology of the obtained tantalum oxyfluoride film is the same as that of the original ammonia tantalum oxyfluoride nanocone film, with a length of less than 1000 nanometers and a maximum width of the cone of less than 500 nanometers.

[0061] like Fig.15 As shown in the top view scanning electron microscope (SEM) photograph of the nanocone tantalum nitride (Ta3N5) supported by the obtained metal tantalum substrate, it can be seen that the morphology of the obtained tantalum nitride film is the same as that of the original tantalum oxygen fluoride nanocone film, with a length of less than 1000 nanometers and a maximum width of the cone of less than 500 nanometers.

[0062] The results of the embodiments show that the present invention can effectively improve the interface between the tantalum-based compound film and the substrate, promote the efficient transfer of charges, and provide a new preparation method for high-performance materials in the fields of photoelectric catalysis, electrocatalysis, microelectronic devices and sensors developed based on tantalum-based functional films.

Claims

1. A method for homogenously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating, characterized in that: Using a metal tantalum substrate or coating as a precursor, hydrothermal treatment is used to in-situ precipitate a homologous metal compound film having a high-quality interface with the tantalum substrate or coating on its surface in a fluorine-containing precursor solution environment; a tantalum oxyfluoride film having a coherent or semi-coherent interface with the tantalum substrate or coating is obtained through a primary heat treatment under different atmospheres; and a secondary heat treatment is then performed under different atmospheres to obtain other tantalum-based compound films having a high-quality interface with the tantalum substrate or coating; The homologous metal compounds are ammonia tantalum oxygen fluoride (NH4)2Ta2O3F6, (NH4)3TaOF6; The atmosphere for obtaining tantalum oxyfluoride by a single heat treatment includes one or a mixture of two or more gases of air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, and sulfur dioxide, the heat treatment temperature is between 100 and 800°C, the heat treatment time is between 5 minutes and 10 hours, and the heating rate is between 1 and 30°C / min; The tantalum oxyfluoride film having a coherent or semi-coherent interface with the tantalum substrate or coating is subjected to secondary heat treatment under different atmospheres, wherein the treatment atmosphere includes one or a mixture of two or more of air, oxygen, nitrogen, argon, ammonia, helium, hydrogen, hydrogen sulfide, borane, methane, acetylene, carbon monoxide, carbon dioxide, and sulfur dioxide, the treatment temperature is between 150 and 1200°C, the treatment time is between 15 minutes and 48 hours, and the heating rate is between 1 and 20°C / min.

2. The method for homogenously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating according to claim 1, characterized in that: The tantalum substrate or coating is made of pure tantalum metal or tantalum-based alloy.

3. The method for homogenously growing a tantalum-based compound film having a high-quality interface on a tantalum substrate or coating according to claim 1, characterized in that: In the fluorine-containing precursor solution, the solute is one of HF, NH4F, NH4HF2 or a mixture of two or more thereof, and the solvent is one of water, ethanol, ethylene glycol or a mixture of two or more thereof.

4. The method for homogenously growing a tantalum-based compound film with a high-quality interface on a tantalum substrate or coating according to claim 1, characterized in that: The hydrothermal treatment process includes gas phase hydrothermal treatment and traditional hydrothermal treatment. The hydrothermal treatment temperature is 80 to 250° C. and the insulation time is 0.5 to 48 hours.

5. The method for homogenously growing a tantalum-based compound film having a high-quality interface on a tantalum substrate or coating according to claim 4, characterized in that: The precursor substrate or coating of vapor phase hydrothermal treatment is suspended above the solution, while the precursor substrate or coating of conventional hydrothermal treatment is immersed in the solution.

Citation Information

Patent Citations

  • Preparation method of metal compound porous nanosheet

    CN112354549A

  • Preparation method of porous metal compound array film

    CN114351239A